Levofloxacin for the treatment of severe refractory BK virus-associated hemorrhagic cystitis in hematopoietic stem cell transplantation recipients: A report of three cases - KANİ, HALUK TARIK; TOPTAŞ, TAYFUR (SPANDIDOS PUBL LTD, 2014)
BK-virus (BKV) is an important etiological agent for late-onset hemorrhagic cystitis (HC) in patients undergoing hematopoietic stem cell transplantation. Late-onset HC causes significant morbidity among these patients. Therapeutic approaches remain predominantly symptomatic. Several treatment options have been used with variable success rates. Cidofovir has the highest specificity against BKV; however, its lack of availability in the majority of countries, high costs and potential nephrotoxic effects limit its,use. The present study reports three cases of severe and prolonged BKV-associated HC (BKHC). HC was resolved in all three of the patients using oral levofloxacin. Thus, levofloxacin may be an effective treatment modality for achieving complete clinical and molecular response in patients with refractory, severe BKHC.
Keywords: BK virus; hemorrhagic cystitis; levofloxacin; hematopoietic stem cell transplantation; BONE-MARROW TRANSPLANTATION; RENAL-TRANSPLANTATION; PREVENTION; VIREMIA